Investigation of wheat producers' knowledge about sustainable weed management (SWM). (2017) - Sayadmansour, Iman; Ebrahimi, Mohammad Sadegh
The present study is an attempt to investigate wheat producers' knowledge about sustainable weed management (SWM) in wheat fields. The population of the study included the wheat farmers in Dooreh-Chegeni region of Iran (N = 1, 650), the samples were selected using the Cochran formula (n = 198). The main data collection instrument used in this study was a questionnaire. The validity of the questionnaire was confirmed through expert judging and protesting. The reliability of the questionnaire was confirmed through Cronbach's alpha coefficient that was equal to (0.818) for learning styles, (0.700) for economic characteristic and (0.723) for social characteristic. The results showed that there is a significant relationship between extension activities and wheat producers' knowledge of integrated weed management. The results also indicate that the knowledge of using an appropriate tillage is the most influential variable on farmers' knowledge of integrated weed management.